2018
DOI: 10.1177/1360780418787209
|View full text |Cite
|
Sign up to set email alerts
|

‘You’re Just Chopped Off at the End’: Retired Servicemen’s Identity Work Struggles in the Military to Civilian Transition

Abstract: Promoting positive transition to retirement and cultural adaption for ex-service personnel has been identified as a priority for both social-science research and for public health policy in the UK. The Royal British Legion aims to provide support to service and retired service personnel, but to date the transition to retirement experiences of older (60-plus) ex-service personnel remain under-researched. In this article, we employ a symbolic interactionist theoretical framework to examine older servicemen’s exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…This ties in with other similar themes seen elsewhere. See for example Cooper et al (2018) and Williams et al (2018), who also touch upon such feelings as not being valued, bullying within the organisation or a lack of support within the organisation, or Walker ( 2012) who categorically discusses attitudes and motivations for departure in his review of leavers in the UK. Apart from the above examples, another commonly cited reason, not unexpectedly, was from respondents who felt they simply needed a change of lifestyle/career and did not mention any particular external reason for leaving.…”
Section: The Transition Experiencementioning
confidence: 99%
“…This ties in with other similar themes seen elsewhere. See for example Cooper et al (2018) and Williams et al (2018), who also touch upon such feelings as not being valued, bullying within the organisation or a lack of support within the organisation, or Walker ( 2012) who categorically discusses attitudes and motivations for departure in his review of leavers in the UK. Apart from the above examples, another commonly cited reason, not unexpectedly, was from respondents who felt they simply needed a change of lifestyle/career and did not mention any particular external reason for leaving.…”
Section: The Transition Experiencementioning
confidence: 99%
“…It was important, therefore, to make a conscious effort to 'stand back' and maintain a critical perspective and analytic distance. Interestingly, R's presuppositions and potential misperceptions often appear to be considered stereotypical of the younger generation by older adults, including by RBL members (Williams et al 2018). Before entering the RBL, R was concerned that she might feel somewhat socially excluded and not particularly welcome at the coffee morning meetings.…”
Section: Researcher Positionalitymentioning
confidence: 99%
“…This concentration on those who suffer to some extent ignores Iversen et al's (2005) 'most do well' findings. Williams et al (2018) believe there is a paucity of social science research examining veterans' support experiences. Williams et al (2018) also found some, especially older, veterans suffer identity challenges turning, for example, to the RBL to construct a 'modified military self'.…”
Section: Veterans' Researchmentioning
confidence: 99%